A model of school improvement specialist coaches (SISC+) in development teaching professionalism: a conceptual review - Gurumoorthy Poobalan; Zulhairul Ramlee; Roslee Talip; Sukuneswari Kaliappan (Human Resource Management Academic Research Society (HRMARS), 2021)
The Program for the Professional Schools Coaches Plus (SISC+) has been introduced in Malaysia since 2013 in order to boost teaching standards and achieve better student achievement in key subject areas, such as Bahasa Melayu and english and mathematics. Teacher training under the SISC + program in the Malaysian education system has various impacts. This research paper is to identify a model of SISC + coaching and mentoring initiatives in enhancing the growth of the teaching profession in line with the third wave of school transformation of the Malaysian Education Development Plan (2021-2025). Researchers discovered that the SISC + model is designed with five action steps based on the Growth Model to help teachers improve their teaching quality and develop teacher professionalism. To gain the necessary information, researchers have used library review. Based on the results, the researcher proposed a model that demonstrated teacher professionalism growth through SISC + in terms of knowledge and skills of pedagogical practices. The model is indirectly will help the middle leaders in school to focus on students achievement and teachers development. The study's results will fill in the gaps in future literature reviews of growth of teaching professionalism and the School Improvement Specialists Coaches Plus.